RSA Blind Signature sebagai dasar pengamanan pada sistem e-voting dengan Prinsip Frictionless User : studi desain dan tinjauan keamanan - Rizky Rahman Judie Putra; Muhamad Nursalman; Ellsya Nabella Nur'allifa (LKP KARYA PRIMA KURSUS, 2025)
Electronic voting (e-voting) systems have emerged as a critical research topic in the fields of information security and modern election technology. However, various studies have shown that e-voting systems still face several vulnerabilities, particularly in security aspects. One prominent weakness often highlighted is the direct involvement of voters in cryptographic technical processes, such as unblinding, which may lead to negligence and technical errors. This aligns with Bartjan Wattel’s assertion that